Museen digital Eine Gedächtnisinstitution sucht den Anschluss an die Zukunft - Kohle, Hubertus (Heidelberg University Publishing (heiUP), 2018)
Museums especially in the Anglosaxon world understand that they have to present themselves in a modern form if they want to be accepted by a younger audience. Internet, social media, virtual and augmented reality, open culture: these are keywords which receive an ever increasing importance in the museum context as well. The book presents a selection of art museums which approach the digital sphere in a creative manner. In this way they try to cope with both their mission to educate and to entertain.